A Critical Disability Reading of Lermontov's "Taman'" - Andrianova, Anastassiya (Disability Studies Quarterly, 2021)
This paper provides a critical analysis of literary disability in Mikhail Lermontov's "Taman'," the most famous story in his semiautobiographical novel, A Hero of Our Time (1838-40). It focuses on three disabled characters: the blind boy, the deaf old woman proprietor, and the mad young woman. These characters have traditionally been treated as projections of the hero-narrator's imagination, as part of the story's Gothic aspects, or as metaphors meant to reveal something about him, thus reducing disability to a textual device. Even when central to the interpretation, disability tends to be read by Lermontov critics as figurative or counterfeit. This project aims, therefore, to reclaim the characters whose disabilities are undermined by the critical tradition. Through a contextualized close reading, it considers how these characters and the narrative events in which they are entangled shape—and ultimately unmake—Pechorin, the eponymous "hero of our time," whose perceptions of dis/ability are challenged by the events of the story he recounts. The paper finds that the depiction of disability in "Taman'" confirms some aspects of our limited historical knowledge about disability (invalidnost') in nineteenth-century Russia and tells us something about conceptions of Romantic literary disability more broadly.